The use of short-term indicators and survey data for predicting turning points in economic activity A performance analysis of the OECD system of CLIs during the Great Recession - Astolfi, Roberto (OECD Statistics Working Papers, 2016)
After reviewing the main features of the statistics available in the MEI to inform policy makers, this paper discusses the performance of the CLIs during the Great Recession. This performance is assessed using both ex-post and real-time analyses. The analyses evaluate the ability of the OECD CLIs to anticipate the peak and the subsequent trough of the Great Recession in G7 countries, and the extent to which the initial signal has been maintained over time